Parks and Protected Areas: Mobilizing Knowledge for Effective Decision-Making - Hvenegaard, Glen; Halpenny, Elizabeth; Bueddefeld, Jill (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Parks and protected areas provide important services to nature and society. Park managers make difficult decisions to achieve their diverse mandates, and need current, relevant, and rigorous information. However, effective use of research provided by social scientists, natural scientists, local people, or Indigenous people is an ongoing challenge. Through case studies, this book examines knowledge mobilization in parks and protected areas, with a focus on successes and failures, barriers and enablers, diverse theoretical frameworks, and structural innovations. This book embraces the generation and use of knowledge, especially natural science, social science, local knowledge, and Indigenous knowledge, in relation to policy, planning, and management of parks and protected areas.